JURIDICAL REVIEW OF BANKRUPTCY IN SIGNING AGREEMENT ON BUYING SELLING OF FLAT IN MEDAN - Heriyanti Heriyanti; Azharuddin Azharuddin; Giovanni Thomasia (Magister Kenotariatan Universitas Pasundan, 2022)
Flats as a place to live with the hope of meeting the needs of the community, especially those who live in cities, there is no reduction in excessive land use and creating infiltration areas for water. With the increase in the number of people in 2010-2020 with an annual average of around 1.25%, it indirectly results in greater decent housing due to the dense population and limited land in the city, thus creating flats. The purpose of the study is to analyze the signing of the Sale and Purchase Binding Agreement (PPJB) for flats, the legal consequences if the developer of the flat goes bankrupt and dispute resolution if the settlement period by the developer defaults on the PPJB flats. The normative juridical method used in this study. With the results, the process of making PPJB flats must meet Article 1320 of the Civil Code as a condition for the validity of the agreement and be made before a Notary. Consequence with a declaration of bankruptcy against the developer resulting in general confiscation of the assets of all assets owned by the developer. Settlement of disputes caused by the inappropriateness of the apartment unit building or the lapse of the settlement period carried out by the developer, is carried out through a non-litigation process (out of court) and if there is no reconciliation, it can be continued with the litigation process (through the court process).